2021
DOI: 10.3390/w13243534
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Prediction of Sustainable Utilization of Water Resources in Chengde City Based on System Dynamics Model

Abstract: In addition to the social economy and the rapid development of industry and agriculture, water demand is increasing and poses challenges in the over-exploitation of water resources. This research establishes a model to assess the sustainable exploitation of water resources based on system dynamics theory and STELLA software, which solves the imbalanced allocation of industrial water, agricultural water and domestic water. The model is composed of two parts: the water quantity system (including economy, populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The policies and planning on the local blueprint were integrated to simulate the water resource variations. Although prior studies pointed out that restricting water demands [ 13 , 57 ], improving water use for industry and wastewater reuse [ 24 ], increasing water saving [ 53 ], installing filtration plants to provide affordable water supply [ 58 , 59 ] are all effective alternatives for achieving a water supply and demand balance, while simulation results in this study revealed that increasing unconventional water supply is more crucial than controlling water demand in improving water supply and demand balance. According to short-term and long-term optimization schemes, to guarantee balanced water supply and demand in the following 2025 and 2035, the domestic water consumption, the tertiary industry water demand, agricultural water use, and unconventional water supply should be consistently adjusted.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The policies and planning on the local blueprint were integrated to simulate the water resource variations. Although prior studies pointed out that restricting water demands [ 13 , 57 ], improving water use for industry and wastewater reuse [ 24 ], increasing water saving [ 53 ], installing filtration plants to provide affordable water supply [ 58 , 59 ] are all effective alternatives for achieving a water supply and demand balance, while simulation results in this study revealed that increasing unconventional water supply is more crucial than controlling water demand in improving water supply and demand balance. According to short-term and long-term optimization schemes, to guarantee balanced water supply and demand in the following 2025 and 2035, the domestic water consumption, the tertiary industry water demand, agricultural water use, and unconventional water supply should be consistently adjusted.…”
Section: Discussionmentioning
confidence: 82%
“…Li et al [ 52 ] constructed a water resource accessibility index model considering five spatial factors to evaluate the water resource accessibility in Southwest China. Wang et al [ 53 ] established a system dynamics model for the sustainable use of water resources in Chengde City, which involves the interaction among industrial, agricultural, and domestic water, but its scenario designs are limited on status quo type of simulated conditions. In this study, we combined variable interaction description and predictive simulation to analyze the water cycle system and proposed an optimal scheme for sustainable management of urban water resources by altering the driving factor values of water supply and water demand.…”
Section: Discussionmentioning
confidence: 99%